Radio - Tollin, Michael; Robbins, Brian; Gains, Herbert W.; Rich, Mike, 1959-; Gooding, Cuba, 1968-; Harris, Ed, 1950-; Woodard, Alfre, 1953-; Merkerson, S. Epatha, 1952-; Winger, Debra, 1955-; Burgess, Don.; Lebenzon, Chris; Rosenstock, Harvey; et al. (Culver City, Calif. : Columbia TriStar Home Entertainment, 2003)
The story of the relationship between a prominent high school football coach in a small South Carolina town and the illiterate, mentally-challenged man nicknamed Radio whom he mentors. Although their friendship raises some eyebrows at first, Radio's growth under the coach's guidance ultimately inspires the local townsfolk.
DVD, region 1, widescreen presentation, Dolby digital.
Closed-captioned.
Cuba Gooding, Jr., Ed Harris, Alfre Woodard, S. Epatha Merkerson, Debra Winger.
Director of photography, Don Burgess ; editors, Chris Lebenzon, Harvey Rosenstock ; music, James Horner ; costume designer, Denise Wingate ; production designer, Clay A. Griffith.
Inspired by a true story.
MPAA rating: PG, for mild language and thematic elements.
Keywords: People with mental disabilities -- Drama; Coaches (Athletics) -- Drama; School sports -- Drama; Feature films; Video recordings for the hearing impaired